Influence of Nanoparticles on Thermophysical Properties of Hybrid Nanofluids of Different Volume Fractions - Abdullah M.Z.; Yu K.H.; Loh H.Y.; Kamarudin R.; Gunnasegaran P.; Alkhwaji A. (MDPI, 2023)
Nanofluids are frequently employed in numerous heat transfer applications due to their improved thermophysical properties compared to a base fluid. By selecting suitable combinations of nanoparticles, hybrid nanofluids can have better thermophysical properties than mono nanofluids. Thus, this study examines the effect of volume fractions of hybrid nanofluids on different thermophysical properties, such as density, thermal conductivity, specific heat, and dynamic viscosity. Thermophysical properties of coppernickel (CuNi) water-based hybrid nanofluids are determined using molecular dynamic (MD) simulation for different volume fractions of 0.10.3%. Results show that the density, thermal conductivity, and viscosity of CuNi hybrid nanofluids increase with volume fraction, whereas the specific heat capacity at a constant pressure decreases with volume fraction. These properties are validated for the base fluid, mono nanofluids, and hybrid nanofluids. Results are in good agreement with previous findings. The thermophysical properties of CuNi hybrid nanofluids significantly improve and have better characteristics for cooling fluids than the base fluid. 2022 by the authors.